Urgency Of Waste Import Regulations For Communities In East Java - Purwanto, Aldira Mara Ditta Caesar; Aryani, Maria Indira (Fakultas Hukum, UPN Veteran Jawa Timur, 2022)
Currently, waste management is a big problem, not only in Indonesia but also throughout the world. Especially after the People's Republic of China (PRC) changed its solid waste import policy on July 18, 2017. The issuance of the National Sword policy aims to limit and tighten imports of plastic waste. The impact of the PRC's policy change is an increase in the flow of waste imports to Indonesia, thus placing Indonesia as a